THE INFLUENCE OF INTERNAL FACTORS ON THE INCIDENCE OF IRRITANT CONTACT DERMATITIS (ICD) IN FISHERMAN IN NIITANASA VILLAGE, LALONGGASUMEETO SUB-DISTRICT, KONAWE DISTRICT: IRRITANT CONTACT DERMATITIS - Titi Saparina; Achmad Saiful; Asfani Yuhadi; Muhammad Ikhsan Akbar (STIKes Mandala Waluya Kendari, 2023)
Background: Irritant contact dermatitis (ICD) ranks 9th as the most common disease at the Lalonggasumeeto Health Center, Konawe Regency, reaching 18 cases in 2021 caused by allergies with complaints such as itching, skin redness, dry skin, and scaly. especially in the Niitanasa village community where the majority of the population work as traditional fishermen who usually go to sea from five in the afternoon until dawn. The purpose of this study was to analyze the influence of internal factors on the incidence of irritant contact dermatitis (ICD) in fishermen in Niitanasa Village, Lalonggasumeeto District, Konawe Regency. Methods: The research method used in this research is analytical research with a cross sectional study design. Where in this research design the measurement of the independent variable and the dependent variable is carried out at the same time. The population in this study were all fishermen in Niitanasa Village, Lalonggasumeeto District, totaling + 45 people. The sample for this study is a portion of the population, namely fishermen in Niitanasa Village, obtained through the use of the Slovin formula and the results obtained are 20 fishermen as a sample. Results: Based on the research conducted by the researchers, the results obtained were a p-value <0.05, which was equal to 0.10, which means that at an α value of 5% there was a significant relationship between length of work and the incidence of irritant contact dermatitis in fishermen, the p-value < 0.05 which is equal to 0.002, which means that at an α value of 5% there is a significant relationship between the use of personal protective equipment and the incidence of irritant contact dermatitis in fishermen and a p-value <0.05 which is equal to 0.002, which means that at an α value of 5% there is a significant relationship between personal hygiene and the incidence of irritant contact dermatitis in fishermen. Conclusion: For fishermen on personal hygiene (personal hygiene) are expected to maintain personal hygiene to maintain health, always get used to washing hands with soap after work and bathing and always change clothes or pants after work and also always wash clothes, pants and gloves with detergent to prevent irritant contact dermatitis ICDThe use of PPE is mandatory for all fishermen.